Malignancy of the maxillary antrum: A case report - Annette M Bhambal; Ajay Bhambal; Ekta Ingle; Navin Anand Ingle (Wolters Kluwer Medknow Publications, 2020)
Malignant tumor of the maxillary sinus is an uncommon tumor of the head and neck. It is a destructive lesion involving the oral and paranasal sinuses. Since it remains confined to the antral region and produces no symptoms, it is usually diagnosed at an advanced stage and has a very poor prognosis and survival rate. We report a case, of a patient who presented with a large painless swelling in the left maxillary region for 3-4 months. Unfortunately, as the tumor was in the advanced stage and involved vital structures, only supportive management could be provided. As the symptoms of malignancy in the maxillary sinus can be non-specific, it can result in late diagnosis and poor prognosis. This case report highlights the necessity of comprehensive knowledge of sinus pathologies for a maxillofacial physician to arrive at an early diagnosis and help for a better prognosis.